Impact of covid-19 on labor force participation in Brazil - Julio Vicente Cateia; Luc Savard; Edivo Almeida de Oliveira (Cogent Economics & Finance, 2022)
This study aims to analyze the impact of Covid-19 on the female's labor force participation (LFP) probability in Brazil in 2020. We found through the probit model that females are about 7 percentage points less likely to participate in the labor force than males. Covid-19 and layoffs decrease by about 7 and 30 percentage points the women's LFP probability, respectively. An additional year of schooling increases female's LFP probability by 14 percentage points. These results are statistically significant at 1%. However, Covid-19-gender interaction term coefficient is not significant. We suggest a rich agenda for women's jobs opportunities in developing countries.
Keywords: C38; D13; E29; O12; 330; economic impact of Covid-19; gender gap; labor force participation; labor market; Brazilian economy